Phytochemical Profile and Antioxidant Activity of Ethanolic Extracts from Selected Wild Medicinal Plants: Azadirachta indica, Acalypha indica, and Muntingia malabura - Nadya Rizkita; Diana Novita Sari; Daning Kinanti Sutama (Green Engineering Society, 2025)
Azadirachta indica, Acalypha indica, and Muntingia calabura are wild plants with antioxidant content capable of treating various diseases. This study aims to evaluate phytochemical compound screening using qualitative tests and to characterize them using FT-IR (Fourier Transform Infrared Spectroscopy) in Azadirachta indica, Acalypha indica, and Muntingia Calabura, as well as to assess total phenolic content (TPC), flavonoid content (TFC), and antioxidant potential. The results showed that Azadirachta indica and Acalypha indica contained alkaloids, flavonoids, tannins, saponins, phenols, glycosides, steroids, and carbohydrates but lacked proteins and triterpenoids. In contrast, Muntingia Calabura leaf extract lacked glycosides, triterpenoids, and carbohydrates. The highest TPC content in Muntingia Calabura extract was 269.88±0.00 mg GAE/gr extract, and the highest TFC was found in Azadirachta indica extract at 676.34±21.85 mg CE/gr extract. The ethanol extract of Azadirachta indica and Muntingia Calabura leaves has very strong antioxidant activity, with IC₅₀ values of 32.76 ± 3.02 ppm and 31.16 ± 1.96 ppm, respectively, while Acalypha indica had an IC₅₀ value of 107.71 ± 3.55 ppm, indicating a moderate level of antioxidant activity. These results support the potential of the three medicinal plants as sources of natural antioxidants. The findings can stimulate further research to isolate key bioactive compounds and perform toxicity tests to support potential applications in the pharmaceutical and food industries.